Applied Model of Nutrient Oxidation in Male Broilers Reared under Different Temperatures - Maksudi, Maksudi (Fakultas Peternakan Universitas Jambi, 2009)
Effects of the environmental temperatures on nutrient oxidation were evaluated in male broiler chickens. The chickens were allocated into twelve cages with six chickens per cage during the first week and three chickens in the following five weeks of experiment. The temperatures were set on T0 = 21o C, T1 = 24oC, and T2 = 28oC. A 22 to 24hourrespiration measurement was made in the middle of each fiveday collection period using an openair circulation respiration unit. The results showed that the increase of temperature decreased protein (OXP) and fat oxidation (OXF; P<0.05), but there was no difference (P>0.05) on carbohydrate oxidation (OXCHO). Lipogenesis from carbohydrate made up the main constitution (69 to 78%) to the total fat retention. In contrast, fat retention from protein (8.8 to 9.6) was the minor contribution, and there was no difference (P<0.05) among the groups. Furthermore, the conversion of dietary fat to the fat retention was increased (12.1 to 21.4) following the increase of the environment temperature. In conclusion, the temperature range of 21 to 28oC used was still in the tolerable hot zone since the oxidation of protein, carbohydrate and fat were not influenced. However, the utilization of protein and fat depended on the environmental temperature except for carbohydrate.